Теоретические аспекты управления изменениями на предприятии на личностном и организационном уровне - Fedosova D. N. (Priority directions of scienceand education development, 2015)
the article deals with theoretical aspects of organizational changes at personal and organisational level, their main characteristics and components, as well as levels of organizational changes.
Keywords: организационные изменения; личностный уровень; организационный уровень; organizational change; personal level; organizational level